"THE WORLD BEGINS AT MY FEET": CHOZA AND THE POETIC PROJECT OF EFRAÍN MIRANDA LUJÁN - Arenas Ulloa, César (2019)
This paper intends to reconstruct an evolutionary line in the poetics of Efraín Miranda Luján from the analysis of a poem from his book Choza (1978). For this, we will try to link their displacements, their marginal position within the spectrum of the generation of 50, with the gradual transformation of their poetic production. Our main hypothesis is that the work of Miranda, excluded from the monopoly of Lima’s literary criticism, was linked to other literary traditions, in particular of the Andean Plateau, so that the recent interest of critics for his work has inserted it into the broader and alternative panorama of the Andean Poetics. We will use as a theoretical framework of analysis the General Textual Rhetoric of Stefano Arduini and the extended TeSWeST II of Tomás Albaladejo, in addition to the contributions of the Cognitive Semantics of George Lakoff and Mark Johnson.